Updated checklist of the order Thysanoptera in Colombia - Ebratt-Ravelo, Everth; Castro-Avila, Angela; Goldaracena-Lafuente, Arturo (Zootaxa, 2024)
We present here the first comprehensive checklist of Thysanoptera in Colombia. This study is based on a literature review, examination of specimens deposited in museums, and fieldwork conducted from 2012 to 2018 across various agroecosystems in the Andean, Caribbean, and Orinoco regions. Our study reports 38 new records of Thysanoptera for Colombia, bringing the total number of documented species to 183.